The pressor and mydriatic effects of tropicamide-phenylephrine combination, plain tropicamide, and plain phenylephrine - Marion Alva Mesina-Bayana, MD; Milagros H. Arroyo, MD (Philippine Journal of Ophthalmology)
Objective: To evaluate the pressor and mydriatic effects of different concentrations of tropicamide and phenylephrine eye drops: tropicamide 0.5% (Mydriacyl), phenylephrine hydrochloride 2.5% (Mydfrin), tropicamide-phenylephrine combination 0.5%/0.5% (Sanmyd-P), and self-prepared mixture (1:1 dilution) of commercially prepared tropicamide 0.5% and phenylephrine 2.5%.